Alarming resistance to third-generation cephalosporins and carbapenems among Enterobacterales colonising pregnant women and neonates in eastern DRC - Théophile Mitima Kashosi; Antonella Minutolo; Carlotta Fiorilla; Marialaura Fanelli; Daniella Ashuza Kagayo; Jean-Baptiste Kajiramugabi; Alfred Cubaka Kabagale; Sandro Grelli; Francesca Pica; Vittorio Colizzi (African Journal of Laboratory Medicine, 2026)
Background: Extended-spectrum cephalosporin-resistant Enterobacterales (ESCR-E) and carbapenem-resistant Enterobacteriaceae (CRE) pose a growing threat to maternal and neonatal health, particularly in low-resource settings. In eastern Democratic Republic of the Congo (DRC), data on antimicrobial resistance in these populations are scarce. Objective: To determine resistance profiles of ESCR-E and CRE among pregnant women, postpartum mothers, and their newborns in South Kivu, eastern DRC. Methods: A cross-sectional multicentre study was conducted from April 2023 to October 2024 in urban and rural health facilities. Rectal swabs or stool samples were collected. Bacterial identification was performed using conventional biochemical galleries, and antimicrobial susceptibility testing was performed by the standard disk diffusion (Kirby–Bauer) method. Results: High rates of ESCR-E and CRE colonisation were found across all groups. Over 90% of ESCR-E isolates were resistant to third-generation cephalosporins and showed multidrug resistance, including to aminoglycosides and fluoroquinolones. Carbapenem-resistant Enterobacteriaceae isolates were resistant to penicillin and cephalosporins but remained susceptible to ceftazidime–tazobactam. These resistance profiles severely limit treatment options in maternal and neonatal care. Conclusion: The high prevalence of multidrug-resistant ESCR-E and CRE in mothers and newborns highlights an urgent need for improved antimicrobial stewardship, resistance surveillance, and infection prevention strategies. The potential use of probiotics to restore gut microbiota and reduce colonisation should also be explored. What this study adds: This study provides the first comprehensive data on ESCR-E and CRE colonisation in mothers and newborns in eastern DRC, revealing alarming multidrug resistance patterns and highlighting the urgent need for targeted stewardship, surveillance, and Infection Prevention and Control strategies in maternal and neonatal care settings.